The role of the tax administration in the provision of public services - Kocherbayeva1, A.A.; Abayev, A.A.; Syzdykova, D.I. (Вестник Карагандинского университета, 2016)
The article deals with the theoretical aspects of tax administration in the context of the provision of public services. It describes the main elements and the structure of the tax administration. The authors have determined that the tax administration is made up of government agency system that have the authority to collect revenue in a budget and a set of rules and regulations governing the tax procedure in the country. By studying the theoretical and methodological issues related to the nature of the tax administration and the tax authority functions in the system of public services, the authors' interpretation of the concept of «tax administration» has been given. The authors proposed the further development of the tax administration.
Keywords: public services; taxes; tax administration; tax authorities; tax law